STRATEGI PENGELOLAAN RUANG BIMBINGAN KONSELING DALAM PENINGKATAN LAYANAN PESERTA DIDIK DI MAS DARUL IHSAN ACEH BESAR - Herawati Boangmanalu; Nurussalami Nurussalami (STKIP Pesisir Selatan, 2026)
This research aims to describe the condition of the guidance and counseling room (BK), analyze the management strategies of the counseling guidance room, and examine its impact on student services at MAS Darul Ihsan Aceh Besar. The research uses a descriptive qualitative approach with data collection techniques involving interviews, observations, and documentation. The research informants consisted of one guidance counselor, one head of the madrasa, and five students selected via purposive sampling. Data analysis was conducted via data reduction, data presentation, and conclusion drawing with validity testing using source and technique triangulation. The research results show that the counseling room at MAS Darul Ihsan has limited dimensions, approximately 3×4 meters, and does not fully support the privacy of counseling services. To address these limitations, the guidance counselor implemented various adaptive strategies, such as multifunctional room arrangements, alternating service schedules, utilizing alternative spaces, and efforts to maintain student confidentiality during the service. These strategies help the counseling guidance services to continue operating effectively and encourage students' openness in participating in counseling services. However, the limitations of privacy and disturbances from the surrounding environment of the counseling guidance room still pose obstacles in the implementation of the services. This study concludes that the creativity of guidance and counseling teachers and institutional support are important factors in maintaining the continuity of counseling services in pesantren-based madrasahs with limited facilities.